Review : Potensi Yoghurt Sinbiotik Kombinasi Rempah Sebagai Suplementasi Probiotik Dan Antioksidan Berbasis Nutrasetikal Bahan Alam Dari Lontar Usadha Taru Pramana Sebagai Kearifan Pengobatan Lokal Bali - Ameilia Ameilia; I Gede Bayu Somantara; Aliya Nur Hasanah (Journal of Pharmaceutical and Sciences, 2023)
Along with the development of COVID-19 cases, health maintenance efforts to maintain and increase endurance are significant. Healthy living efforts that need to be implemented are by regulating the intake of nutritional supplementation of both macronutrients and micronutrients. One type of nutraceutical food with complex nutrients that has the potential to be used as a nutraceutical for supplementation efforts is yogurt. Traditionally, yogurt is also mentioned in the Balinese medical wisdom, namely, Usadha. In Usadha, yogurt combines ingredients found in Lontar Usadha Taru Pramana (Usadha, which contains various medicinal plants). The method used to compile this article is a systematic review literature study. Relevant information was collected from Google Scholar, Science Direct, ProQuest, Pubmed, and EBSCO. Scopus, Sinta, or Garuda-indexed articles published in the last five years were selected. Based on the literature search, it is known that the addition of each turmeric, ginger, secang, and cinnamon extract to yogurt can improve the physicochemical quality and nutritional content of the yogurt, especially antioxidants, thus contributing to health maintenance and being able to maintain the probiotic stability of yogurt. The combination of spiced yogurt with ginger, turmeric, secang wood, and cinnamon rhizomes can be used as probiotic-antioxidant supplementation to support a healthy lifestyle related to maintaining the immune system.